A review of the health educational strategies for a sustainable guinea worm eradication programme in the Tolon-Kumbungu District of the Northern Region, Ghana - Mustapha, Issahaku (2011)
A thesis presented to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for the award of a Master of Science degree in Health Education and Promotion.